2017
DOI: 10.5114/reum.2017.72623
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin modulation of the activation of PYK2 in peripheral blood mononuclear cells from patients with lupus nephritis

Abstract: IntroductionProline-rich tyrosine kinase 2 (PYK2) provides important signals during the activation of lymphocytes, which is essential in autoimmune diseases. Systemic lupus erythematosus (SLE) is a representative autoimmune disease, and lupus nephritis (LN) is one of its most severe complications. Although glucocorticoid-binding immuno-suppression is the first-line therapy for patients with LN, the common and severe side effects of such treatment call for new strategies to improve long-term prognosis and life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Contrary to this, another study revealed that administration of low doses of curcumin (0.1 and 1.0 µg/mL) to cultured CD4 + cells from patients with SLE significantly (p < 0.001) modulated the Th17/Treg balance without affecting healthy subjects (187). Similar to this in vitro experiment, low-dose curcumin (0.1 µg/mL) inhibited the expression and activation of PYK2 in peripheral blood mononuclear cells (PBMCs) and reduced the proliferation of PBMCs in patients with lupus nephritis (188).…”
Section: Polyphenolssupporting
confidence: 56%
“…Contrary to this, another study revealed that administration of low doses of curcumin (0.1 and 1.0 µg/mL) to cultured CD4 + cells from patients with SLE significantly (p < 0.001) modulated the Th17/Treg balance without affecting healthy subjects (187). Similar to this in vitro experiment, low-dose curcumin (0.1 µg/mL) inhibited the expression and activation of PYK2 in peripheral blood mononuclear cells (PBMCs) and reduced the proliferation of PBMCs in patients with lupus nephritis (188).…”
Section: Polyphenolssupporting
confidence: 56%
“…15 This PYK2 reduction was accompanied by an associated decrease in 24hr proteinuria (p < 0.01). 15 Serological markers. The same group, Wang et al, showed that complement C3 levels were negatively correlated with curcumin inhibition.…”
Section: Human Models: In-vivomentioning
confidence: 85%
“…In vitro studies have also revealed that curcumin decreases total IgG, serum levels of BAFF following toll‐like receptor (TLR) 4 stimulation, B‐cell activation in MRL/lpr mice, and reduces lupus nephritis in MRL/lpr mice, which may represent an overall therapeutic strategy in the management of SLE (Abrahams et al, 2019). Moreover, curcumin inhibited the upregulation and stimulation of proline‐rich tyrosine kinase 2(PYK2) in vitro in PBMCs obtained from patients with lupus nephritis (M. Wang et al, 2017). PYK2 is a nonreceptor protein tyrosine kinase that is essentially connected to focal adhesion kinase (FAK) and implicated in blocking costimulatory molecules (including CD40L and CTLA‐4) and cell growth (Cong, Wang, Konrad, Schoeb, & Elson, 2009).…”
Section: Autoimmune Skin Diseasementioning
confidence: 99%
“…In vitro studies have also revealed that curcumin decreases total IgG, serum levels of BAFF following toll-like receptor (TLR) 4 stimulation, B-cell activation in MRL/lpr mice, and reduces lupus nephritis in MRL/lpr mice, which may represent an overall therapeutic strategy in the management of SLE(Abrahams et al, 2019). Moreover, curcumin inhibited the upregulation and stimulation of proline-rich tyrosine kinase 2(PYK2) in vitro in PBMCs obtained from patients with lupus nephritis (M Wang et al, 2017)…”
mentioning
confidence: 99%